An H2O2 Molecule Stabilized inside Open‐Cage C60 Derivatives by a Hydroxy Stopper. Issue 2 (9th December 2021) - Huang, Guanglin; Hasegawa, Shota; Hashikawa, Yoshifumi; Ide, Yuki; Hirose, Takashi; Murata, Yasujiro
Abstract: An H2 O2 molecule was isolated inside hydroxylated open‐cage fullerene derivatives by mixing an H2 O2 solution with a precursor molecule followed by reduction of one of carbonyl groups on its orifice. Depending on the reduction site, two structural isomers for H2 O2 @open‐fullerenes were obtained. A high encapsulation ratio of 81 % was attained at low temperature. The structures of the peroxosolvate complexes thus obtained were studied by 1 H NMR spectroscopy, X‐ray analysis, and DFT calculations, showing strong hydrogen bonding between the encapsulated H2 O2 and the hydroxy group located at the center of the orifice. This OH group was found to act as a kinetic stopper, and the formation of the hydrogen bonding caused thermodynamic stabilization of the H2 O2 molecule, both of which prevent its escape from the cage. One of the peroxosolvates was isolated by HPLC, affording H2 O2 @open‐fullerene with 100 % encapsulation ratio, likely due to the intramolecular hydrogen‐bonding interaction. Abstract : Hydroxylated open‐cage fullerene derivatives enabled the complete isolation of a single H2 O2 molecule as the stable peroxosolvate in the solid state. Crystallographic and computational analyses revealed that the arrangement of the hydroxy group and intramolecular hydrogen‐bonding contribute to the kinetic and thermodynamic stabilization of the H2 O2 molecule.